BAKING WORKSHOP TO ENHANCE PRACTICAL SKILLS AND ENTREPRENEURIAL INTEREST AMONG FACULTY OF ECONOMICS AND BUSINESS STUDENTS AT MALIKUSSALEH UNIVERSITY - Nurainun; Heriyana; Sari Yulis Terfiadi; Zulfan; Miftahul Jannah (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2026)
This community service activity aimed to enhance practical baking skills and foster entrepreneurial interest among students of the Faculty of Economics and Business, Malikussaleh University. The activity was conducted through a baking training program organized by the Innopreneur Business Lab, involving 25 students as participants. The training consisted of three stages: preparation, implementation, and evaluation. The implementation stage included the delivery of materials on baking fundamentals, culinary business opportunities, product packaging, pricing strategies, and hands-on practice in producing klapertart and caramel pudding. Evaluation was carried out through direct observation, documentation, and discussions with participants. The results showed that participants actively engaged in the training and successfully completed the production of klapertart and caramel pudding according to the demonstrated procedures. The activity not only improved participants’ practical baking skills but also increased their understanding of entrepreneurial opportunities in the culinary sector. The combination of theoretical knowledge and practical experience provided participants with valuable insights into developing dessert-based business ventures. Therefore, the baking training program proved to be an effective approach for strengthening practical competencies and encouraging entrepreneurial interest among university students.